Desafios escolares na compreensão dos diretores brasileiros: evidências da relação com o saber - Souza, Aline Cristina de (Universidade Federal de São Carlos, 2022)
Throughout the social transformations, the school has been modifying the different sectors that compose it, such as, for example, the applicability of school management, directing it towards collective participation through democratic management. However, it is known that many challenges were and still are within the school. Given this, the present study aimed to analyze what school directors identify as the main challenges of the school and their solutions, according to the Relationship with Knowledge (RcS). To this end, exploratory qualitative research was delimited, which included the application of an open questionnaire directed to the entire national territory, thus covering all school principals. The instrument had two open questions - the first turned to the challenges experienced by school directors and the respective solutions found by them to remedy the problems experienced, and finally, the second question referred to the school challenge in terms of quality of teaching. The questions were addressed to 150,000 schools belonging to the five Brazilian regions, of which 1,372 were returned, which constituted the central sample of this study. However, only complete responses were selected for the research analyses, which is equivalent to 1313 responses. From this, the data treatment was carried out, subdivided into two main stages of analysis. The first was based on the use of the Iramuteq software, which presents quantitative data regarding the cloud and class of words, informing the frequency of its use, grouping them and, thus promoting approximation percentages. This resource was used seeking to refine the reading of the answers for the content analysis, which complements the first stage of analysis, through which three main categories were created that guide the entire study and, consequently, help to understand the Relation of Knowledge of school principals. The categories are: Knowledge – relational or the absence of relationships with families; knowledge – practical in dealing with the physical structure or infrastructure of the school, and knowledge – practical or the absence of student learning. From these, the theory of Relation with Knowledge (RcS) was used in order to understand the relational, practical and objective knowledge of school principals. In a concise data analysis, knowledge was obtained about the main common challenges of schools presented by the five Brazilian regions, namely: family participation, infrastructure and learning and learning difficulties. While the challenges that differ occur due to the particularities of each region, such as transport, human resources, materials, physical structure, etc. It was also possible to observe that despite the territorial extension of Brazil, school challenges and their solutions are recurrent in the five regions, which demonstrates a problem in the education system that tends to be unique for a country with continental extension. In addition, it is considered that the challenges observed as different demonstrate that the particularities of the schools are buried by the most latent difficulties, in this case, those common to all schools. With regard to the challenges facing schools regarding the quality of teaching and learning, it was observed that they run into structural and social issues that precede them, since minimum standards do not promote teaching with excellence.
School challenges in the understanding of brazilian principals: evidence of the relationship with knowledge
Keywords: Relação com o saber; Diretores escolares; Desafios da Escola; Soluções; Qualidade do Ensino; Relationship with knowledge; School Directors; School challenges; Solutions; Teaching quality; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL